Strategi Pemasaran Media Sosial Yang Efektif Untuk Seniman Muda - Raihan Kaisa Fauziah Duha; Rizki Putri Devira Mrp; Isnaini Fadhilah; Osberth Sinaga (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Social media has become an effective marketing tool for young artists to introduce and promote their work to a broader audience. This study aims to analyze social media marketing strategies that can enhance the visibility and sales of artistic works. The research employs a literature review approach with content analysis of relevant studies published between 2018 and 2024. The findings indicate that effective social media marketing strategies for young artists consist of three main aspects: personal branding, algorithm optimization, and monetization strategies. Strong personal branding through visual consistency and storytelling has been proven to increase audience engagement and strengthen artists’ competitiveness on digital platforms. In terms of algorithm optimization, the use of short-form videos, consistent posting frequency, and SEO implementation play a vital role in expanding the reach of artistic content. Meanwhile, monetization strategies such as the utilization of e-commerce platforms, subscription-based models, and Non-Fungible Tokens (NFTs) have proven effective in converting audience engagement into a more stable source of income. This study contributes to the development of digital marketing literature within the creative industry and serves as a practical guide for young artists in optimizing social media as a marketing tool. The findings also provide a foundation for the development of more effective and adaptive digital marketing strategies in response to the dynamic and evolving trends of the creative industry.